Síndrome de Burnout y satisfacción laboral en docentes de una institución de educación superior, Medellín, 2008 (2009)
ABSTRACT: To determine prevalence of burnout syndrome, its relationship with several demographic and labor variables, and labor satisfaction in teachers who were working in the National Faculty of Public Health (Universidad de Antioquia) during the second semester 2008. Methodology: a descriptive crosssectional study was carried out in three independent, random, and representative samples, according to the type of contract under which professors were working for the university. A total of 89 professors were surveyed, using Maslach (mbi) validated scale and Duran teaching labor satisfaction scale. Results: prevalence of presumable burnout cases was 19.1% (18), highlighting that 49.4% (39) were under a presumable risk of suffering the syndrome. According to the kind of contract, full-time teachers presented the highest prevalence (25%). The general average of labor satisfaction in educators was 123 points (possible score: 22-154). Conclusions: in general, teachers reported low levels of emotional tiredness, depersonalization and personal fulfillment (the latter being a negative indicator). Furthermore, no differences were found in scores of job satisfaction by sex, age or the type of contract.